Application Of The Discovery Learning Model In Increasing Student Activity - Yasin, Muhammad; Nasution, Fira Rusdianti (Indonesian Scientific Publication, 2023)
The aims of this research are the urgency of implementing the Discovery Learning Learning Model in Islamic Religious Education Subjects at North Sangatta 1 Vocational School, what is the Process of Implementing the Discovery Learning Learning Model in Increasing Student Activities in Islamic Religious Education Subjects at North Sangatta 1 State Vocational School, and how to have a positive impact on students by implementing the Discovery Learning Learning Model in Islamic Religious Education Subjects. This research uses qualitative methods. Type of field research, where to obtain accurate data the researcher comes directly to the research location, namely SMK Negeri 1 Sangatta Utara, using a qualitative research approach. In this research, researchers used data collection techniques in the form of observation, interviews, documentation with descriptive techniques. In analyzing this data, the author uses data condensation, data presentation, and drawing conclusions or verification. The findings of this research are (1) the discovery learning model is very good at helping students easily understand the subject matter. (2) In the process of implementing the learning model using the discovery learning learning model using lesson plans as a reference, of course there are three parts, the first is the introductory part consisting of (orientation, apperception, motivation, and providing references), the second is the core part where the application of the discovery learning model is included in This section consists of (stimulation, problem statement, questions/problem identification, data collection, data management, proof and drawing conclusions). (3) The positive impact on students from the application of the discovery learning model in Islamic Religious Education subjects is: Can improve students' ability to solve problems, Encourages active involvement of students, and this Learning Model prepares students for independent learning.